Penafsiran Al-Sya’rawi Terhadap Ayat-Ayat yang Berkaitan dengan Al-Nafs - Sigit Ardiansyah (Jurnal Iman dan Spiritualitas, 2021)
The Qur'an is a guide for humanity that contains everything related to all creatures, it was just that in interpreting the meaning of the Qur'an there are still many who do not know and master the meaning of these verses. The word Al-Nafs is a word found in the Qur'an in various forms. The Qur'an mentions the term Al-Nafs as many as 298 mentions in 270 verses contained in 63 letters. Of the many mentions there are different meanings, namely: the Essence of Allah SWT, the Spirit, the inner side of humans, Person, offspring, the human self and something that refers to what is contained in humans that produces behavior. This research focuses on finding out the term Al-Nafs in the interpretation of Al-Sya'rawi, then examining it to find out how it is interpreted in interpreting the verses related to al-Nafs and how efforts to shape and make al-Nafs itself have a good impact on the community. one's self. In this study, the researcher used a qualitative method, this method was used to give birth to a thought figure from one of the commentators who were studied on a selected theme. And describe the character's thoughts by connecting and returning the original meaning carefully to all data, either in the form of opinions or statements. The research sources consist of the interpretation of Al-Sha'rawi and various literature related to this research.